The Role of the Kinin System and the Effect of Des-Arginine9-Bradykinin on Coagulation and Platelet Function in Critically Ill COVID-19 Patients: A Secondary Analysis of a Prospective Observational Study - Edinger, Fabian; Edinger, Sophia; Schmidt, Götz; Koch, Christian; Sander, Michael; Schneck, Emmanuel; Justus Liebig University Giessen (My University, 2024)
The effect of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) on the coagulation system is not fully understood. SARS-CoV-2 penetrates cells through angiotensin-converting enzyme 2 (ACE2) receptors, leading to its downregulation. Des-arginine9-bradykinin (DA9B) is degraded by ACE2 and causes vasodilation and increased vascular permeability. Furthermore, DA9B is associated with impaired platelet function. Therefore, the aim of this study was to evaluate the effects of DA9B on platelet function and coagulopathy in critically ill coronavirus disease 2019 (COVID-19) patients. In total, 29 polymerase-positive SARS-CoV-2 patients admitted to the intensive care unit of the University Hospital of Giessen and 29 healthy controls were included. Blood samples were taken, and platelet impedance aggregometry and rotational thromboelastometry were performed. Enzyme-linked immunosorbent assays measured the concentrations of DA9B, bradykinin, and angiotensin 2. Significantly increased concentrations of DA9B and angiotensin 2 were found in the COVID-19 patients. A negative effect of DA9B on platelet function and intrinsic coagulation was also found. A sub-analysis of moderate and severe acute respiratory distress syndrome patients revealed a negative association between DA9B and platelet counts and fibrinogen levels. DA9B provokes inhibitory effects on the intrinsic coagulation system in COVID-19 patients. This negative feedback seems reasonable as bradykinin, which is transformed to DA9B, is released after contact activation. Nevertheless, further studies are needed to confirm our findings.
Keywords: ddc:610